2017
DOI: 10.1111/ijn.12569
|View full text |Cite
|
Sign up to set email alerts
|

Developing a medical picture book for reducing venipuncture distress in preschool‐aged children

Abstract: We recommend the picture book be routinely read and used during venipunctures to decrease procedural distress in preschool-aged children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…According to Langford, 6 to 12 year-old children acquire logical thinking and their distress could be reduced realistically through explanation and brie ng before the procedure (22). A similar study in preschool age children did not nd clear bene t of a picture book on reducing distress levels during IV catheterization (12). We hypothesized that school aged children 6-12 would bene t from the picture book orientation given this advanced development.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…According to Langford, 6 to 12 year-old children acquire logical thinking and their distress could be reduced realistically through explanation and brie ng before the procedure (22). A similar study in preschool age children did not nd clear bene t of a picture book on reducing distress levels during IV catheterization (12). We hypothesized that school aged children 6-12 would bene t from the picture book orientation given this advanced development.…”
Section: Discussionmentioning
confidence: 85%
“…Distress was measured by Observation Scale of Behavior Distress_ Revised (OSBD_R), a standard scale to measure distress validated by Elliot et al (18) and utilized in in similar studies (12,16). Speci cally for an Iranian population, Ghazavi et al con rmed the reliability of this scale (r=0.70) (17).…”
Section: Evaluation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, early palliative care, including communication with the patients about the illness and its prognosis, symptom assessment and management, support for coping, and regular follow-ups have been found to improve the quality of life [47]. Some studies suggest that reading and using picture books before procedures promote children's understanding and reduce stress [48] and anxiety [49]. Picture books about cancer could be used to communicate about cancer with children.…”
Section: Advantages Of Picture Booksmentioning
confidence: 99%
“…Children's illustrated books are unique sources for attractive instructions since these books aim to provide the reader with brief, fun, colorful, and readable material (20). Some studies reported that medical picture books are very instrumental to reduce anxiety among pre-school children during and after intravenous placement procedure.…”
Section: Introductionmentioning
confidence: 99%